Avaliação de técnicas de homogeneização de solo para detecção de cistos de Giardia duodenalis - Oliveira, Clarisse M. Boni de (2012)
The soil is an important vehicle for the transmission of the protozoan Giardia duodenalis, which causes the global disease giardiosis, gastroenteritis of changeable severity. The objective of this study was to evaluate different process of homogenization soil samples in order to know which of them is most effective for cysts detection and recovery. Four treatments of homogenization were performed with four replicates of each one. Each replicate contained 10g of soil contaminated with a 500 cysts, moistened with phosphate-buffered saline and shaked according to the following treatments: vortex for 2 minutes; magnetic stirrer for 10 minutes, homogenization during 30 minutes in a rotary mixer; and manual homogenization for 5 minutes. After homogenization, the samples remained resting for 5 minutes on the bench in order to sediment and separate the coarser soil particles. Then the supernatant and the finer particles were centrifuged at 1050 x g for 10 minutes and the immunomagnetic separation was performed in the resulting pellet. The cysts were labeled and enumerated by immunofluorescence assay. There was no significant different found in the mean value of magnetic stirrer (81.07), rotary mixer (70.40) and manual homogenization (49.60). However, the replicates of rotary mixer showed themselves more homogeneous when separating the coarser particles from the finer ones that would be taken to centrifugation. Therefore, this treatment was chosen as the most effective and reproducible process. The mean from the vortex samples was the lowest (8.45) showing a significant difference from the others.